Disparate Tuberculosis Disease Development in Macaque Species Is Associated With Innate Immunity - Dijkman, Karin; Vervenne, Richard A. W.; Sombroek, Claudia C.; Boot, Charelle; Hofman, Sam O.; van Meijgaarden, Krista E.; Ottenhoff, Tom H. M.; Kocken, Clemens H. M.; Haanstra, Krista G.; Vierboom, Michel P. M.; Verreck, Frank A. W. (Frontiers in Immunology, 2019)
While tuberculosis continues to afflict mankind, the immunological mechanisms underlying TB disease development are still incompletely understood. Advanced preclinical models for TB research include both rhesus and cynomolgus macaques (Macaca mulatta and Macaca fascicularis, respectively), with rhesus typically being more susceptible to acute progressive TB disease than cynomolgus macaques. To determine which immune mechanisms are responsible for this dissimilar disease development, we profiled a broad range of innate and adaptive responses, both local and peripheral, following experimental pulmonary Mtb infection of both species. While T-cell and antibody responses appeared indistinguishable, we identified anti-inflammatory skewing of peripheral monocytes in rhesus and a more prominent local pro-inflammatory cytokine release profile in cynomolgus macaques associated with divergent TB disease outcome. Importantly, these differences were detectable both before and early after infection. This work shows that inflammatory and innate immune status prior to and at early stages after infection, critically affects outcome of TB infection.